2019
DOI: 10.1155/2019/7142438
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of MMP-12, TIMP-4, and Neutrophil Elastase in PBMCs and Exhaled Breath Condensate in Patients with COPD and Their Relationships with Disease Severity and Acute Exacerbations

Abstract: Objective. The purpose of this study was to compare matrix metalloproteinase-12 (MMP-12), neutrophil elastase (NE), and tissue inhibitor of metalloproteinase-4 (TIMP-4) in peripheral blood of patients with chronic obstructive pulmonary disease (COPD) and controls. At the same time, MMP-12, NE, and TIMP-4 in exhaled breath condensate (EBC) were also evaluated. Methods. Peripheral blood and EBC samples from COPD patients and healthy controls were collected. In serum and EBC, MMP-12, NE, and TIMP-4 proteins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Moreover, serum NE protein level was significantly higher in COPD ‘exacerbator with emphysema phenotype’ patients compared with healthy subjects. This is consistent with previous studies,23 24 which indicated that NE levels in serum and peripheral blood mononuclear cells of COPD patients are much higher than in healthy subjects. In addition, the serum NE level of severe–very severe patients (GOLD 3&4) was significantly higher than that of mild–moderate patients (GOLD 1&2).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, serum NE protein level was significantly higher in COPD ‘exacerbator with emphysema phenotype’ patients compared with healthy subjects. This is consistent with previous studies,23 24 which indicated that NE levels in serum and peripheral blood mononuclear cells of COPD patients are much higher than in healthy subjects. In addition, the serum NE level of severe–very severe patients (GOLD 3&4) was significantly higher than that of mild–moderate patients (GOLD 1&2).…”
Section: Discussionsupporting
confidence: 93%
“…levels promotes the migration and differentiation of monocytes in lung tissue, amplifying the inflammatory process [44][45][46]. The chronic inflammation of the lungs results in alterations in the parenchyma architecture, a process known as tissue remodeling, due an unbalance between active MMPs and its inhibitors, TIMP [47,48]. In concordance with this notion, CS group presented, in association with pulmonary neutrophilia, alveolar enlargement as well as loss of alveolar parenchyma, collagen deposition, and destruction of elastic fibers.…”
Section: Plos Onementioning
confidence: 77%
“…Neutrophils also activate MMPs through production of elastase (47,48), so we reasoned that elevated neutrophil-mediated inflammation observed in the Il17ra −/− mice could be due to dysregulated MMPs and could impact the process of wound healing (49,50). The increased levels of Mmp10 and Mmp3 in the WT tissue during OM were diminished in the Il17ra −/− tissue (Figure 5A).…”
Section: Enhanced Neutrophil Response In Il-17ra-deficient Micementioning
confidence: 99%